PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI - Zikri Dola Agusti; Endrawati Endrawati; Lisa Amelia Herman (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This This study aims to examine the effect of corporate social responsibility (CSR) and institutional ownership on firm value, with financial performance as a mediating variable. The research employs a quantitative approach with an associative research design. The data used are secondary data obtained from financial statements, annual reports, and sustainability reports. The population consists of all energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period, totaling 69 companies. The sampling technique applied is purposive sampling. Data analysis is conducted using STATA 17.0 software. The results show that CSR has no effect on either financial performance or firm value. Institutional ownership has an effect on financial performance but does not influence firm value. Meanwhile, financial performance significantly affects firm value but fails to mediate the relationship between CSR and institutional ownership with firm value